2007
DOI: 10.1063/1.2769759
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration effect of Ni electrodes on the resistive switching characteristics of NiO thin films

Abstract: The effects of Ni and Ni0.83Pt0.17 alloy electrodes on the resistance switching of the dc-sputtered polycrystalline NiO thin films were investigated. The initial off-state resistances of the films were similar to that of Pt∕NiO∕Pt film. However, after the first cycle of switching, the off-state resistance significantly decreased in the films with Ni in the electrode. It can be attributed to the migration of Ni from electrodes to the NiO films. The improvement in data dispersion of switching parameters is expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Many methods have been proposed for the binary metal oxides to suppress the variations, such as reducing the active device area by plug-bottom electrode [3], inserting IrO 2 buffer layer to stabilize the local oxygen migrations [4], creating the locally strong electric field by process control [5], reducing the effective film thickness by Ni migration [6], and modifying the resistive switching characteristics by Ti top electrode [16], [17].…”
Section: Improvement Of Resistive Switching Characteristicsmentioning
confidence: 99%
“…Many methods have been proposed for the binary metal oxides to suppress the variations, such as reducing the active device area by plug-bottom electrode [3], inserting IrO 2 buffer layer to stabilize the local oxygen migrations [4], creating the locally strong electric field by process control [5], reducing the effective film thickness by Ni migration [6], and modifying the resistive switching characteristics by Ti top electrode [16], [17].…”
Section: Improvement Of Resistive Switching Characteristicsmentioning
confidence: 99%
“…Cobalt was found to be completely suppressed and a Fe-Cr oxide containing outer sphere (89% Fe, 9.78% Cr; Table S2 †) was created during the surface oxidation process. We speculate that the diffusion of ions caused by a momen-tum transfer e − → M + at high current densities 52 as discussed in one of our earlier contributions 20 is responsible for the changes of the surface composition as determined by XPS spectroscopy and summarized in Table S2. † XPS data of untreated X20CoCrWMo10-9 steel have been shown in our earlier contribution.…”
Section: 21mentioning
confidence: 99%
“…Their results show that if the thickness of resistive switching materials increases, the data dispersion of switching parameters would be deteriorated. 19 However, in our measurement results, we did not observe these phenomena. On the other hand, the constitution of a thin FeO x transition layer would affect the device's electrical characteristics and performances in our previous studies.…”
Section: F Materials Examination and Analysismentioning
confidence: 45%
“…3(b), the set power was calculated to slightly reduce and even saturate with increasing stopped voltage. Of note, although the statistics of set voltage have slight increased with stopped voltage, it did not mean that the switching thickness would change dramatically, 19 where examined its cross-section image by TEM (not shown here). In addition, it is suggested that the thin FeO x transition layers constitution would affect electrical characteristics, 15 especially the distribution of oxygen vacancies and free oxygen species, are changed in different phases and recovered by different stopped voltage values.…”
Section: Resistive Switching Mechanism For CC Effectmentioning
confidence: 94%